LEPROSY NEUROPATHY : CLINICAL PRESENTATION - Rizki Rahamatullah Noer; Shahdevi Nandar Kurniawan (Journal of Pain, Headache and Vertigo, 2023)
Leprosy is a chronic infection caused by the bacteria M. leprae and causes damage to the skin and peripheral nervous system outside the brain and spinal cord, including the skin, mucous membranes of the nose, testicles, and eyes. This disease develops slowly over a long period, ranging from 6 months to 40 years, and can cause skin lesions and secondary defects. Leprosy is a common and treatable cause of peripheral neuropathy in many tropical and subtropical countries. Neuropathy is a condition that causes damage to the function and structure of the sensory, autonomic, and motor nerves in the peripheral nervous system. Complications of neuropathy can include loss of sensory abilities and muscle weakness. Impaired sensory nerve function is often the first symptom that appears in leprosy neuropathy. Therefore, early detection and treatment of neuropathy in leprosy is very important to prevent disability.